Development of an Analytical Protocol for Determination of Cyanide in Human Biological Samples Based on Application of Ion Chromatography with Pulsed Amperometric Detection - Ewa Jaszczak; Marek Ruman; Sylwia Narkowicz; Jacek Namieśnik; Żaneta Polkowska (Journal of Analytical Methods in Chemistry)
A simple and accurate ion chromatography (IC) method with pulsed amperometric detection (PAD) was proposed for the determination of cyanide ion in urine, sweat, and saliva samples. The sample pretreatment relies on alkaline digestion and application of Dionex OnGuard II H cartridge. Under the optimized conditions, the method showed good linearity in the range of 1–100 μg/L for urine, 5–100 μg/L for saliva, and 3–100 μg/L for sweat samples with determination coefficients (R)>0.992. Low detection limits (LODs) in the range of 1.8 μg/L, 5.1 μg/L, and 5.8 μg/L for urine, saliva, and sweat samples, respectively, and good repeatability (CV < 3%, n=3) were obtained. The proposed method has been successfully applied to the analysis of human biological samples.